NATIONAL PATRIOTIC EDUCATION AS THE BASIS OF THE EDUCATIONAL SYSTEM OF MODERN EDUCATIONAL INSTITUTIONS - Skirda, Tetiana (Theoretical and Methodical Problems of Children and Youth Education, 2022)
The article updates the issue of national-patriotic education in the educational system of general secondary and out-of-school education institutions as a systematic and purposeful activity. It is emphasized that national-patriotic education in the educational system of general secondary and out-of-school education institutions involves the use of forms and methods of work that are aimed at involving students in the deep layers of national culture and spirituality, the formation of national worldview positions, ideas, views and beliefs in children and youth based on the values of national and world culture. The readiness of teachers to develop, test and introduce pedagogical innovations into the educational process as a necessary component of professional activity was analyzed. It was determined that the majority of teachers are ready to implement innovative forms of work, are open to improving or updating their own educational practice by creating, adapting and popularizing new effective forms and methods of work. The content of the most effective forms of work on national-patriotic education in the educational system of institutions of general secondary and out-of-school education is characterized and disclosed, the directions of work of an educational institution on national-patriotic education are outlined. Attention is focused on the importance of using such methods and forms of activity in pedagogical practice, which are aimed at revealing the individuality of the child’s personality. The conclusions confirm that the educational space of the educational institution should become a source of humanistic values and meanings for the child, which will direct it to self-realization, self-affirmation, development and growth.